Orthodontic pain. (2nd April 2020) - Grewal, Sukhraj; Harris, Lydia MJ; Ponduri, Sirisha; Naish, Hywel; Ellis, Pamela; Sandy, Jonathan R; Ireland, Anthony J
Abstract : Pain is a common side-effect of orthodontic treatment. The aetiology of orthodontic pain, pain pathways and pain management will be described. CPD/Clinical Relevance: An understanding of the cause and subsequent management of orthodontic pain is essential for any orthodontist in order to improve patient co-operation and satisfaction with treatment.